Etude d'une population taurine de race Baoule en Cote d'Ivoire - Tidori, E.; Serres, H.; Richard, D.; Ajuziogu, J. (1975)
Studies the growth characteristics of Baoule cattle at Bouake husbandry centre, Cote d'Ivoire. Discussions on animal morphology, productivity, and disease resistance included with specific reference to age at first calving, calving interval, calf growth, calf mortality, fattening on stylosanthes, meat yield and milk yield.